Effectiveness and safety of ICIs for the treatment of advanced CC: a systematic review and meta-analysis - Ibibulla, Nurbia; Lu, Pengfei; Nuerrula, Yiliyaer; Hu, Xueqin; Aihemaiti, Mulati; Wang, Yubo; Zhang, Hua (Frontiers in Immunology, 2025)
BackgroundThe use of immune checkpoint inhibitors has recently become a promising and innovative therapeutic option for patients suffering from advanced recurrent or metastatic cervical cancer(CC), and several studies of immunotherapy have been published or have revealed stage-by-stage results at international congresses. Nevertheless, there is a lack of meta-analyses of ICIs for advanced CC in past Meta-analysis.MethodThis meta-analysis rigorously followed the PRISMA guidelines, using Review Manager V.5.4 and R(v4.2.2) software for data synthesis. Hazard ratios, risk ratios, and risk differences were calculated, with statistical significance assessed via the Mantel-Haenszel test. Heterogeneity was evaluated using the Higgins I2 statistic, and sensitivity analyses were conducted if heterogeneity surpassed 50%. The efficacy outcomes examined and gathered included the overall response rate (ORR), progress-free survival, overall survival(OS), and the adverse events (AEs), crucial for understanding the efficacy and safety of ICIs in advanced cervical cancer.ResultThe results demonstrate significant efficacy and manageable safety of ICIs in advanced cervical cancer. In RCTs, ICIs improved OS (HR = 0.66, 95% CI: 0.58-0.75, P < 0.00001) and PFS (HR = 0.67, 95% CI: 0.59-0.75, P < 0.0001), with a 34% and 33% reduction in death and progression risks, respectively. ORR was higher in ICIs groups (RR = 1.39, 95% CI: 1.08-1.80, P = 0.01). Single-arm studies supported these findings (ORR: RD = 0.31, 95% CI: 0.22-0.40, P < 0.0001). Safety profiles were manageable, with comparable TRAEs in RCTs and higher incidences in single-arm studies. Subgroup analysis revealed superior OS benefits in PD-L1-positive patients (CPS ≥1, HR = 0.65, 95% CI: 0.50–0.84, P = 0.001) and significant efficacy in squamous cell carcinoma (HR = 0.67, P < 0.00001). Sensitivity analysis confirmed robust OS results (I² = 0%) and stable ORR despite heterogeneity. Risk of bias was low to moderate.ConclusionOur meta-analysis reveals that immune checkpoint inhibitors (ICIs) significantly prolong overall survival in advanced cervical cancer patients, reducing the hazard ratio for death. Despite heterogeneity in outcomes, ICIs offer substantial treatment benefits. Further research is needed to optimize usage and monitor AEs.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO, identifier CRD42023387789.